2017
DOI: 10.4236/oja.2017.71001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Density on Sound Absorption Coefficient of Fibre Board

Abstract: For acoustic applications such as theaters, cinema halls, auditoriums the data on acoustic properties i.e. sound absorption coefficient and sound transmission loss are required to evaluate the acoustic behavior of panel products and to facilitate the necessary design computations. Fibre boards are widely used in private and commercial buildings, but not much data are available on acoustic efficiency of fibre boards. The study was carried using acoustic pulse tester based on standing wave method for evaluating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 9 publications
4
15
0
Order By: Relevance
“…In the 30 mm ones, Placuna placenta shell has a wider broadband frequency than the other two shells. Associated with density material, this result is in accordance with other research conducted by Nandawar et al, [25] where decreasing density on fiber boards improves sound absorption ability (see Figure 3). Placuna placenta with 30 mm thick and density 1.392 gram/cm 3 had the best sound absorption followed by Anadara granosa with density 1.643 gram/ cm 3 .…”
Section: Sound Absorption Coefficientsupporting
confidence: 92%
See 2 more Smart Citations
“…In the 30 mm ones, Placuna placenta shell has a wider broadband frequency than the other two shells. Associated with density material, this result is in accordance with other research conducted by Nandawar et al, [25] where decreasing density on fiber boards improves sound absorption ability (see Figure 3). Placuna placenta with 30 mm thick and density 1.392 gram/cm 3 had the best sound absorption followed by Anadara granosa with density 1.643 gram/ cm 3 .…”
Section: Sound Absorption Coefficientsupporting
confidence: 92%
“…Research by Wang and Torng [23] and Latief, et al found the increment of density could increase the sound absorption coefficient in low frequencies [24]. Different results were released in research by Nandanwar, et al where low density fiber boards possess a higher sound absorption coefficient than high density fiber boards [25]. For research on the effect of density on Sound Transmission Loss performance (STL), two studies conducted by Ko, et al and Narang identified that additional cavities on the metal material could improve the STL performances [26,27].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sound absorption coefficients of all the specimens increased as the frequency increased, in line with the results obtained for typical porous sound-absorbing materials such as glass wool and rock wool (Or et al 2017). The sound absorbing ability of a material depends on the amount of air trapped in its pores because of the friction that generates between the incident sound energy and the air layer inside the material (Nandanwar et al 2017). When comparing fiberboards D-1 through D-3, higher sound absorption ability was observed for the least dense sample, due to its higher porosity (D-1: 89.7%, D-2: 86.2%, D-3: 83.0%).…”
Section: Acoustical Properties Sound Absorption Performancesupporting
confidence: 85%
“…Sound waves can travel through different mediums, including gas, liquid, and solids, but with different speeds dependent on the medium. Typically, sound travels faster in a liquid or solid medium, for example, water or a steel bar, than in gas medium (20)(21)(22)(23).…”
Section: Sound As a Mechanobiological Stimulusmentioning
confidence: 99%